2006
DOI: 10.1063/1.2193435
|View full text |Cite
|
Sign up to set email alerts
|

Extremely sharp carbon nanocone probes for atomic force microscopy imaging

Abstract: A simple and reliable catalyst patterning technique combined with electric-field-guided growth is utilized to synthesize a sharp and high-aspect-ratio carbon nanocone probe on a tipless cantilever for atomic force microscopy. A single carbon nanodot produced by an electron-beam-induced deposition serves as a convenient chemical etch mask for catalyst patterning, thus eliminating the need for complicated, resist-based, electron-beam lithography for a nanoprobe fabrication. A gradual, sputtering-induced size red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 19 publications
0
60
1
Order By: Relevance
“…The transparent conductive oxide (TCO) thin films are semiconductor materials with low resistivity and high transparency over a large spectral range, from visible to near infrared. The interest about these materials has been increased in the last years because they play an important role in a variety of usages such as flat panel displays, solar energy cells, and opto-electronic devices [1][2][3][4][5]. The TCO films must have wide band gap, low resistivity and high transmittance in the particular spectral region where the device operates.…”
Section: Introductionmentioning
confidence: 99%
“…The transparent conductive oxide (TCO) thin films are semiconductor materials with low resistivity and high transparency over a large spectral range, from visible to near infrared. The interest about these materials has been increased in the last years because they play an important role in a variety of usages such as flat panel displays, solar energy cells, and opto-electronic devices [1][2][3][4][5]. The TCO films must have wide band gap, low resistivity and high transmittance in the particular spectral region where the device operates.…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery in 1991 [2], CNTs are interesting One-dimensional structures that have unique electronic, mechanical and chemical properties [3]. Thus far, CNTs have been attracted much attention for use in various types of electronic devices such as field emission displays [4], scanning probes [5,6] and field effect transistor (FET) [7] because of their exceptional electronic and mechanical properties [8,9]. The nano tubes are promising candidates of ideal field emission electron sources because of their high aspect ratio geometry and small tip radius of curvature [10].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has been devoted to developing one-dimensional carbon nanostructures. Chen et al have achieved aligned carbon nanocones on a solid substrate via a resist-free e-beam induced deposition (EBID) of carbon masks combined with electric-field controlled CVD techniques [6]. Kempa et al have demonstrated a technique of growing periodically arranged carbon nanotubes using a catalyst pattern produced from a mask with the use of self-assembled submicron spheres [7].…”
Section: Introductionmentioning
confidence: 99%